The influence of high-order chromatin state in the regulation of stem cell fate. (16th December 2022) - Chen, Xinpeng; Lin, Haiyan; Li, Guohong
Abstract : In eukaryotic cells, genomic DNA is hierarchically compacted by histones into chromatin, which is initially assembled by the nucleosome and further folded into orderly and flexible structures that include chromatin fiber, chromatin looping, topologically associated domains (TADs), chromosome compartments, and chromosome territories. These distinct structures and motifs build the three-dimensional (3D) genome architecture, which precisely controls spatial and temporal gene expression in the nucleus. Given that each type of cell is characterized by its own unique gene expression profile, the state of high-order chromatin plays an essential role in the cell fate decision. Accumulating evidence suggests that the plasticity of high-order chromatin is closely associated with stem cell fate. In this review, we summarize the biological roles of the state of high-order chromatin in embryogenesis, stem cell differentiation, the maintenance of stem cell identity, and somatic cell reprogramming. In addition, we highlight the roles of epigenetic factors and pioneer transcription factors (TFs) involved in regulating the state of high-order chromatin during the determination of stem cell fate and discuss how H3K9me3-heterochromatin restricts stem cell fate. In summary, we review the most recent progress in research on the regulatory functions of high-order chromatin dynamics in the determination and maintenance of stem cell fate.